2012
DOI: 10.1093/intimm/dxs071
|View full text |Cite
|
Sign up to set email alerts
|

IgGs containing light chains of the λ- and κ- type and of all subclasses (IgG1–IgG4) from the sera of patients with systemic lupus erythematosus hydrolyze myelin basic protein

Abstract: Human myelin basic protein (hMBP)-hydrolyzing activity was recently shown to be an intrinsic property of antibodies from systemic lupus erythematosus (SLE) patients. Here, we present the first evidence demonstrating a significant diversity of different fractions of polyclonal IgGs (pIgGs) from SLE patients in their affinity for hMBP and in the ability of pIgGs to hydrolyze hMBP at different optimal pH values (5.3-9.5); the pH profiles of IgG1, IgG2, IgG3 and IgG4 were unique. IgGs containing the λ-type of ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
157
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(168 citation statements)
references
References 36 publications
11
157
0
Order By: Relevance
“…The relative contribution of SLE IgGs of different subclasses to the total proteolytic activity of IgGmix was estimated in a similar way: IgG1 (73.0 ± 3.4%) > IgG2 (19.1 ± 1.8%) > IgG3 (6.7 ± 0.3%) > IgG4 (1.2 ± 0.2%). These data provided the first evidence that SLE IgGs of all types possess MBP-hydrolyzing activity, but they differ in the relative contribution into the total activity of proteolytic activity of polyclonal abzymes [76]. Kappa-IgGs and lambda-IgGs hydrolyzed MBP within a wide range of pH values (5.3-9.5) and showed comparable pH dependencies, while the pH profiles for IgG1-IgG4 were unique (Figure 17).…”
Section: Lupus 70mentioning
confidence: 84%
See 4 more Smart Citations
“…The relative contribution of SLE IgGs of different subclasses to the total proteolytic activity of IgGmix was estimated in a similar way: IgG1 (73.0 ± 3.4%) > IgG2 (19.1 ± 1.8%) > IgG3 (6.7 ± 0.3%) > IgG4 (1.2 ± 0.2%). These data provided the first evidence that SLE IgGs of all types possess MBP-hydrolyzing activity, but they differ in the relative contribution into the total activity of proteolytic activity of polyclonal abzymes [76]. Kappa-IgGs and lambda-IgGs hydrolyzed MBP within a wide range of pH values (5.3-9.5) and showed comparable pH dependencies, while the pH profiles for IgG1-IgG4 were unique (Figure 17).…”
Section: Lupus 70mentioning
confidence: 84%
“…In addition, the level of lymphocyte proliferation as well as cell apoptosis in different organs including bone marrow of healthy MRL-lpr/lpr and EAE mice, at stages of their prediseases and deep pathologies were also comparable [32]. In addition, it was shown that abzymes hydrolyzing MBP are formed in the early stages of human MS, unlike in later stages of SLE, while the reverse situation was observed for abzymes with DNase activity [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87]. One gets the impression that SLE and MS differ greatly in their initial stages but become to some extent more similar at the later stages of these diseases.…”
Section: Cell Apoptosis In Sle Prone Micementioning
confidence: 99%
See 3 more Smart Citations